Complete genome sequence of Dyadobacter fermentans type strain (NS114(T)) - Lang, Elke (Michigan State University, 2009)
Dyadobacter fermentans (Chelius and Triplett, 2000) is the type species of the genus Dyadobacter. It is of phylogenetic interest because of its location in the Cytophagaceae, a very diverse family within the order ‘Sphingobacteriales’. D. fermentans has a mainly respiratory metabolism, stains Gram-negative, is non-motile and oxidase and catalase positive. It is characterized by the production of cell filaments in aging cultures, a flexirubin-like pigment and its ability to ferment glucose, which is almost unique in the aerobically living members of this taxonomically difficult family. Here we describe the features of this organism, together with the complete genome sequence, and its annotation. This is the first complete genome sequence of the sphingobacterial genus Dyadobacter, and this 6,967,790 bp long single replicon genome with its 5804 protein-coding and 50 RNA genes is part of the Genomic Encyclopedia of Bacteria and Archaea project.